How Can Intranasal Oxytocin Research Be Trusted? A Systematic Review of the Interactive Effects of Intranasal Oxytocin on Psychosocial Outcomes. (September 2020) - Mierop, A.; Mikolajczak, M.; Stahl, C.; Béna, J.; Luminet, O.; Lane, A.; Corneille, O.
Over the past two decades, research about the role of oxytocin (OT) in human behavior has grown exponentially. However, a unified theory of OT effects has yet to be developed. Relatedly, growing concerns about the robustness of conclusions drawn in the field have been raised. The current article contributes to this debate by reporting on and discussing key conclusions from a systematic review of published studies addressing the interactive effects of intranasal OT (IN-OT) administration on psychosocial outcomes in a healthy population. The review indicates that (a) tested interactive IN-OT effects were highly heterogeneous; (b) for most published interactions, no replication was attempted; (c) when attempted, replications were largely unsuccessful; (d) significance was unrelated to sample size; (e) statistical power was critically low and unrelated to the rate of significant results; and (f) research practices were characteristic of an exploratory approach. This concerning state of affairs makes it virtually impossible to tease apart true from false interactive IN-OT effects. We provide constructive directions on the basis of this observation and positive predictive value simulations for future research that should help extract true effects from noise and move the IN-OT field forward.